2018
DOI: 10.1186/s12881-018-0707-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel SLC6A8 mutation associated with intellectual disabilities in a Chinese family exhibiting creatine transporter deficiency: case report

Abstract: BackgroundX-linked creatine transporter deficiency (OMIM#300036,CRTR-D) is characterized by cerebral creatine deficiency, intellectual disabilities, severe speech impairment, seizures and behavioral problems. Mutations in the creatine transporter gene SLC6A8, a member of the solute-carrier family 6 mapped to Xq28, have been reported to cause the creatine transporter deficiency.Case presentationThe proband presented at 5 yrs. 1 month of age with delays in intellectual and development, seizures and behavioral pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Rasd2 and Igfbp5 were identified by a recent study as candidate genes associated with epileptogenicity in KA model of TLE 49 and Fxyd7 to be altered after seizure preconditioning using pilocarpine model 50 . Human studies reported Cdkn1a to be upregulated in patients with epilepsy 51 and deficiency in Slc6a8 was reported to result in intractable epilepsy and cognitive impairment 52 . Although, with the given dataset, we are not able to deduce any direct involvement in seizure modulation, many of those genes were previously described to be associated with neuronal excitability, seizures or epilepsy.…”
Section: Changes In the Expression Of Par Bzip Transcription Factors mentioning
confidence: 99%
“…Rasd2 and Igfbp5 were identified by a recent study as candidate genes associated with epileptogenicity in KA model of TLE 49 and Fxyd7 to be altered after seizure preconditioning using pilocarpine model 50 . Human studies reported Cdkn1a to be upregulated in patients with epilepsy 51 and deficiency in Slc6a8 was reported to result in intractable epilepsy and cognitive impairment 52 . Although, with the given dataset, we are not able to deduce any direct involvement in seizure modulation, many of those genes were previously described to be associated with neuronal excitability, seizures or epilepsy.…”
Section: Changes In the Expression Of Par Bzip Transcription Factors mentioning
confidence: 99%
“…The chorionic villus was sampled from the third fetus at 14 weeks of pregnancy. DNA was extracted as previously described [19]. The first fetus was not available for molecular testing.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, it is worth noting that congenital CRT deficiency is associated with autism, epilepsy, neurological defects, and intellectual disabilities [276,277]. This neurometabolic disorder is part of the Cr deficiency syndrome [52].…”
Section: What Is the Basis Of Creatine Transport?mentioning
confidence: 99%